Thinker, Learner, and Practitioner: Using an Insider’s Lens to Explore Critical, Cultural, and Global Consciousness Through Multicultural Literature - Dias, Dany (Language and Literacy / Langue et littératie, 2022)
Literacy research highlights a need to explore the way literacy is used in the classroom and how current practices engage students with aspects of humanity and social justice. This doctoral research took place as a classroom inquiry that examined the potential for multicultural literature to expand adolescent learners’ worldviews and shape their perceptions as global citizens. From a constant stance of reflexivity, this teacher researcher recalls a dynamic eighth-grade language arts classroom as they engaged with multicultural books and real-life events, before and during a pandemic. This paper focuses on select themes and subthemes emerging from pedagogical practices used in the classroom throughout the study. Notions of time, space, place, and identity detail an intentional and purposeful pedagogy as learners interacted with literacy within and beyond their classroom community.